Pengaruh Metode Role Play terhadap Kemampuan Berbicara Bahasa Jepang Siswa SMAN 7 Padang - Wensih Fantri Lisna; Reny Rahmalina (Universitas Negeri Padang, 2021)
Japanese lessons in Indonesian schools have limited learning methods, especially in ability to speak Japanese which has an impact on student’s interest in speaking Japanese. Therefore, a method is needed such as a role play method to help improve student’s speaking ability in Japanese. The purpose of this study was to determine the effect of the role play method on ability to speak Japanese in class X IPS 4 SMAN 7 Padang. This research was a quantitative research with a quasi-experimental type, with a posttest only control group design. While the sampling technique used purposive sampling technique. The sample in this study were students of class X IPS 4 with a total 32 students, 16 students as the control class and 16 students as experimental class. The data in this study are the posttest result from the control class and the experimental class. The result of data analysis,obtained t_count and t_table a significant level of 0,05% is 2.04 with degree of freedom dk=n1+n2. This means t_count > t_table (2,72>2,04). The hypothesis is accepted, because t_count > t_table. So, the role play method has an effect on the ability to speak Japanese in class X IPS 4 students of SMAN 7 Padang.